Strategi Pengawasan OJK terhadap Layanan Perbankan Digital dalam Menjamin Kepatuhan Hukum dan Perlindungan Konsumen - Syafri, Muhammad Irvan; Abdurrahman, Harits; B, Baidhowi (Media Hukum Indonesia (MHI), 2025)
The rapid development of information technology has significantly transformed the banking sector, particularly through the digitalization of financial services. The Financial Services Authority (OJK) plays a crucial role in regulating and supervising this sector to ensure the stability of the financial system and consumer protection. While digitalization offers efficiency and broader access, new challenges arise, such as data security risks, technology misuse, and the presence of unregistered digital financial institutions. In this context, OJK functions not only as a regulator but also as a facilitator for safe and sustainable innovation. Through a risk-based approach and the development of a regulatory sandbox, OJK strives to create an inclusive and secure financial ecosystem. This study employs a normative legal method to analyze regulations and best practices in supervising digital financial services in Indonesia.